Respon Pertumbuhan Vegetatif Tanaman Padi (Oryza sativa L.) terhadap Aplikasi Kombinasi EM4 dan Trichoderma sp. - Anisa tismardi; Filza Yulina Ade; Irma Leilani Eka Putri; Violita (Jurnal Biogenerasi, 2026)
Rice (Oryza sativa L.) plays a crucial role as a primary food source in Indonesia, and efforts to improve its growth need to be directed toward sustainable cultivation systems. The use of soil microorganisms, such as Effective Microorganisms-4 (EM4) and Trichoderma sp., is a widely studied alternative due to its ability to improve the condition of other microorganisms obtained from the soil around the roots and support plant growth. This study was conducted to determine the effect of a combination of EM4 and Trichoderma sp. on the vegetative growth of rice plants. The study was conducted from December to February 2026 in Pagambiran Ampalu Village, Lubuk Begalung District, using a completely randomized design (CRD) with six treatments and four replications. Observed parameters included plant height, number of leaves, number of tillers, and plant dry weight. Data were analyzed using analysis of variance (ANOVA) followed by Duncan's test at a 5% significance level. The results showed that the combination of EM4 and Trichoderma sp. improved several